Data-Driven Analytics for China’s Overseas Construction Projects in the Contexts of the Maritime Silk Road and Global Maritime Network - Zhi-Hua Hu (Complexity)
The Belt and Road (BR) Initiative (BRI) is usually examined in geopolitics perspectives, while the studies ignored the consistency of the BRI with the world economy and China’s historical international business. This study developed a maritime big data system to analyze global interactions upon the global maritime network generated from the system. The BR is coupled with Chinese overseas construction projects (COCPs) in the context of the global maritime network by data-driven analytics methods. A network is developed by extracting the spatial interactions among maritime ports, and time and spatial analyzing methods are used for vessel flows among maritime ports. Then, nine analytical experiments are conducted to examine the relations between COCP and BRI. The figure of the BR emerges from COCP and the maritime network. The BR region and especially the 21st Century Maritime Silk Road (MSR) had emerged as a definite shape ten years ago. The BRI creates additional opportunities in developing the Silk Road Economic Belt (SREB) and the connectivity between BR and the world. The policy implications considering China, regions, and global communities are further be studied. The BR is investigated by using the big data coupled with the COCP other than just depicting from geographical and economic views.